Validity of Nordic-style questionnaires in the surveillance of upper-limb work-related musculoskeletal disorders - Descatha, Alexis; Roquelaure, Yves; Chastang, Jean François; Evanoff, Bradley; Melchior, Maria; Mariot, Camille; Ha, Catherine; Imbernon, Ellen; Goldberg, Marcel; Leclerc, Annette (Scandinavian Journal of Work, Environment & Health, 2007)
' ' OBJECTIVES ': 'The study aimed at comparing results of standardized Nordic-style questionnaires with those of clinical examinations in two surveys on upper-limb work-related musculoskeletal disorders. ' ' METHODS ': 'The “repetitive task” survey (1757 workers in 1993–1994 and 598 workers in 1996–1997) studied risk factors of the disorders among those exposed to repetitive work. The “Pays de la Loire” survey (2685 workers in 2002–2003) was part of a population-wide surveillance system. In both surveys, each worker completed a Nordic-style questionnaire and underwent a standardized clinical examination. The presence of at least one upper-limb work-related musculoskeletal disorder was compared, with an evaluation of sensitivity, specificity, and kappa values, with a clinical examination as reference. In the second survey, a global score of a numerical scale for the severity of symptoms at the time of the examination was evaluated in the same way (plus ROC curves). ' ' RESULTS ': 'Agreement between the questionnaire and the examination differed in the two surveys, from kappa 0.22 [95% confidence interval (95% CI) 0.19–0.23] in the “Pays de la Loire” survey to kappa 0.77 (95% CI 0.74–0.80) in the “repetitive task” survey in 1993–1994. Overall, sensitivity was excellent (82.3–100%). The specificity varied, from 51.1% in the “Pays de la Loire” survey to 82.4% for the ≥2 score based on the severity of symptoms in the survey. ' ' CONCLUSIONS ': 'Nordic-style questionnaires exploring symptoms in the past year can be useful tools for monitoring upper-limb work-related musculoskeletal disorders, especially if they include numerical rating scales of symptom severity. Physical examination remains essential for a medical or clinical diagnosis.
Keywords: epidemiologic surveillance; Nordic-style questionnaire; predictive value; sensitivity; specificity; upper-limb; work-related musculoskeletal disorder